2020
DOI: 10.3390/antibiotics9120870
|View full text |Cite
|
Sign up to set email alerts
|

Fragments of a Wheat Hevein-Like Antimicrobial Peptide Augment the Inhibitory Effect of a Triazole Fungicide on Spore Germination of Fusarium oxysporum and Alternaria solani

Abstract: There are increasing environmental risks associated with extensive use of fungicides for crop protection. Hence, the use of new approaches using natural plant defense mechanisms, including application of plant antimicrobial peptides (AMPs), is of great interest. Recently, we studied the structural–function relationships between antifungal activity and five hevein-like AMPs from the WAMP (wheat AMP) family of Triticum kiharae Dorof. et Migush. We first discovered that short peptides derived from the central, N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 51 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Synergies between peptides and other antimicrobials have also been reported. Fragments of a wheat hevein-like peptide increased the inhibitory effect of the triazole fungicide Folicur ® on spore germination of pathogenic fungi [70]. In a preliminary work, it was reported that short peptides derived from the central, Nand C-terminal regions of the peptide WAMP-2 worked sinergically with fungicide Folicur EC250 ® to inhibit spore germination of Fusarium ssp and Alternaria alternata [71].…”
Section: Hdp As the Active Principle Of Phytosanitary Products For Cr...mentioning
confidence: 99%
“…Synergies between peptides and other antimicrobials have also been reported. Fragments of a wheat hevein-like peptide increased the inhibitory effect of the triazole fungicide Folicur ® on spore germination of pathogenic fungi [70]. In a preliminary work, it was reported that short peptides derived from the central, Nand C-terminal regions of the peptide WAMP-2 worked sinergically with fungicide Folicur EC250 ® to inhibit spore germination of Fusarium ssp and Alternaria alternata [71].…”
Section: Hdp As the Active Principle Of Phytosanitary Products For Cr...mentioning
confidence: 99%